RUNTUHNYA HEGEMONI NEGARA DALAM MENENTUKAN KURIKULUM PESANTREN - Hefni, Moh. (STAIN PAMEKASAN, 2012)
AbstractThis article explains how the state commits a hegemony against pesantren (Islamic boarding school) and how pesantren performs a counter-hegemony. The writer uses the concept of Hegemony purposed by Gramsci. State hegemony against pesantren has started since the collonialism of the East Indies through the penetration of modernization discourse issued to the pesantren circle. The hegemony continued in the era of new order (orde baru) by publishing an integrated-letter of akcnowledgment (SKB) released by three ministriesÂ in 1975. It claimed that pesantren and madrasah became the part ofÂ national education. As a result, the compostion of Madrasah instructional material must be 60% for general science and the rest was for religious science. Yet, when the state hegemony comes to the peak point pesantren undergoes a counter-hegemony. Pesantren still maintains its distinct educational system independently; the educational system includes the curriculum as well as the instructional process. This firm act results a state acceptance. Since 1998 the governmentÂ has released aÂ letter of acknwoledment of degree equating. This model of pesantren known as pesantren muâadalah (equation). The graduation certificate of pesantren could be used for any purposes, as the certificate of MA and SMA do.. Kata-kata kuncihegemoni, hegemoni tandingan, negara, kurikulum, pesantren, muâadalah